2014
DOI: 10.1155/2014/870271
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for Treating Whiplash Associated Disorder: A Systematic Review of Randomised Clinical Trials

Abstract: The aim of this systematic review was to determine the effectiveness of acupuncture for the treatment of whiplash associated disorder (WAD). Twenty databases were searched from their inceptions to Oct. 2013. Randomised clinical trials (RCTs) of acupuncture (AT), electroacupuncture (EA), or dry needling (DN) for the treatment of WAD were considered eligible. The risk of bias was assessed using the Cochrane tool. Six RCTs met the inclusion criteria. Most of the included RCTs have serious methodological flaws. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 28 publications
1
35
0
Order By: Relevance
“…Other studies have used acupuncture in various forms, with a recent systematic review of 6 included RCTs concluding that there may be some effects on pain but no effect on disability. 23 The results of our study are somewhat similar: we found small but significant effects on pain thresholds but not perceived pain and small effects on disability. Additionally, our results indicated that the real dry-needling intervention resulted in small decreases in the psychological measures of pain catastrophizing and posttraumatic stress symptoms, but the clinical relevance of these findings is questionable.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Other studies have used acupuncture in various forms, with a recent systematic review of 6 included RCTs concluding that there may be some effects on pain but no effect on disability. 23 The results of our study are somewhat similar: we found small but significant effects on pain thresholds but not perceived pain and small effects on disability. Additionally, our results indicated that the real dry-needling intervention resulted in small decreases in the psychological measures of pain catastrophizing and posttraumatic stress symptoms, but the clinical relevance of these findings is questionable.…”
Section: Discussionsupporting
confidence: 79%
“…This is at odds with previous studies of acupuncture-like techniques and exercise interventions where the effects (if present) are mostly observed immediately after the intervention. 23,34 Our data indicate that there was improvement in the primary outcome measures (approximate 10% decrease in NDI-unadjusted outcomes; score of 2.0 on GPE indicating some recovery) from baseline to the immediate 6-week post-intervention assessment www.painjournalonline.com 639 Table 2 Unadjusted outcomes (mean and SD) for each treatment group at 0, 6 weeks, 12 weeks, 6 months, and 12 months. Treatment effects at 6 weeks, 12 weeks, 6 months, and 12 months (mean difference and 95% confidence interval).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Acupuncture was found to significantly reduce pain intensity while improving functional mobility, and health-related quality of life. (50,51) Finally, three reviews considered the effects of acupuncture on a wide variety of chronic pain syndromes. (52)(53)(54) Risks Mild adverse events (e.g.…”
Section: Evidencementioning
confidence: 99%
“…Acute WAD injuries are treated with education regarding early physical activity and mobilization, with specific exercises to help with movement and strength in injured regions [12][13][14]. Similarly, other complementary or alternative treatments are also commonly used by physiotherapists within regular clinical practice to treat WAD [15], such as acupuncture (primarily Western medical acupuncture) [16][17][18][19][20][21][22]. Indeed the current National Institute for Health and Care Excellence (NICE) guidelines recommended acupuncture treatment for non-specific neck pain (within 4-12 weeks of injury) [23].…”
Section: Introductionmentioning
confidence: 99%